Portuguese Consensus Document Statement in Diagnostic and Management of Atypical Hemolytic Uremic Syndrome - Azevedo, A (2018)
Among thrombotic microangiopathies (TMA), the hemolytic uremic syndrome associated with dysregulation of the alternative complement pathway (aHUS) is one of the most challenging diseases a nephrologist can face. By the end of the XXth century, the complement’s role was unraveled with the discovery that mutations in the factor H coding gene were responsible for aHUS. But it was the acknowledgment that pharmacological C5-9 blockage provided a cure for aHUS that fostered the interest of the nephrology community in the genetics, pathophysiology and therapeutics of, not only of aHUS, but TMA in general. The molecular genetics of aHUS is technically demanding and, as such, in Portugal (alike many other European countries) a single laboratory emerged as a national reference center. The fact that all samples are evaluated in a single center provides a unique opportunity for data collection and a forum for discussion for all those interested in the field: immunologists, molecular geneticists, pathologists and nephrologists. The current consensus document emerged from such a discussion forum and was sponsored by the Portuguese Society of Nephrology. The goal is more to portray the Portuguese picture regarding the diagnostic approach and therapeutic options than to extensively review the state of the art of the subject. The accompanying documents that are published as supplementary data are in line with that goal. They range from the informed consent and clinical form to be sent together with the biological samples for genetic testing, to the appendix regarding the actual sampling and storing conditions. The document is also intended to set an example for future documents and independent discussion forums on other kidney diseases for which emerging diagnostic and/or therapeutic strategies are reaching clinical practice.